Incidence of neuromyelitis optica spectrum disorders in China: a large cohort study using claim data. Issue 1 (31st January 2022) - Wu, Yiqun; Yang, Mo; Gao, Pei; Wang, Zijing; Wu, Junhui; Wang, Jiating; Xu, Quangang; Zhou, Huanfen; Wu, Tao; Wu, Weiping; Wei, Shihui; Hu, Yong-Hua
Abstract : Objectives: Population-based studies estimating the incidence of neuromyelitis optica spectrum disorders (NMOSDs) in Asia are limited, and the relationship between latitude and incidence has been scarcely investigated. We aimed to estimate the incidence of NMOSDs in Chinese adults and explore their relationship to latitude. Design: Cohort study based on data from the Urban Employee Basic Medical Insurance in China. Participants: 177 million people were followed from 2016 to 2017 in 20 provinces. Primary outcome measures: The incidence rate was estimated by Poisson distribution and reported as age-adjusted and sex-adjusted rates using the standard population. Results: There were 1313 incident NMOSD cases, with an overall incidence of 0.41 (95% CIs: 0.39 to 0.43) per 100 000 person-years. The incidence in females was higher, with a female-to-male IRR of 4.52. The incidence increased with age, peaking at 55–64 years in females and 65–74 years in males and then decreasing thereafter. The female-to-male IRRs were higher in those <55 years. The association between latitude and incidence was not statistically significant. Conclusions: The incidence of NMOSD in Chinese adults was 0.41 per 100 000 person-years. There is no latitude gradient observed. Sex and age influence the risk of NMOSD, suggesting the role of genetic, hormonal and other related factors in the pathophysiology.